Effect of Coconut Fiber and Coconut Shell Charcoal Composition on the Properties of PVC-Reinforced Composite Brake Pads - Aap Pandriana; Kurniawan Kurniawan; Sagir Alva (Universitas Mercu Buana, 2025)
The increasing concern over the health hazards associated with asbestos-based brake pads has driven the development of eco-friendly alternatives using natural fiber-reinforced composites. This study aims to fabricate and evaluate a sustainable brake pad material using coconut fiber as reinforcement, coconut shell charcoal powder as filler, and polyvinyl chloride (PVC) as the matrix. The composite was manufactured using the hot press method at a temperature of 180°C and a pressure of 7 MPa, conditions selected to optimize resin curing and interfacial bonding. A key focus of this research was to investigate the effect of solvent volume (cyclohexanone) used in the PVC resin preparation on the mechanical properties of the resulting composites. Three composite formulations were prepared with a constant composition of 70% coconut fiber, 5% charcoal powder, and 25% PVC resin, but with varying amounts of cyclohexanone solvent (200 mL, 150 mL, and 100 mL). The results revealed that reducing solvent content led to higher resin viscosity, which improved matrix–fiber bonding and increased both tensile strength and surface hardness. The optimal formulation—PVC Resin 3 with 100 mL of solvent—achieved a maximum tensile strength of 7.7 MPa and Shore D hardness of 72.2 HD, both of which meet the SAE J661-1997 standards for brake pad materials. This study confirms that solvent content is a critical factor influencing the density, strength, and durability of the composite. The findings support the feasibility of utilizing coconut-based agricultural waste in producing environmentally friendly brake pads with adequate mechanical performance.